Mortality from cancer in people with severe mental disorders in Emilia Romagna Region, Italy. Issue 12 (9th September 2021) - Grassi, Luigi; Stivanello, Elisa; Belvederi Murri, Martino; Perlangeli, Vincenza; Pandolfi, Paolo; Carnevali, Fabio; Caruso, Rosangela; Saponaro, Alessio; Ferri, Mila; Sanza, Michele; Fioritti, Angelo; Meggiolaro, Elena; et al.
Abstract: Objective: To examine cancer‐related mortality in patients with severe mental disorders (SMI) in the Emilia Romagna (ER) Region, Northern Italy, during the period 2008–2017 and compare it with the regional population. Methods: We used the ER Regional Mental Health Registry identifying all patients aged ≥18 years who had received an ICD‐9CM system diagnosis of SMI (i.e., schizophrenia or other functional psychosis, mania, or bipolar affective disorders) during a 10‐year period (2008–2017). Information on deaths (date and causes of death) were retrieved through the Regional Cause of Death Registry. Comparisons were made with the deaths and cause of deaths of the regional population over the same period. Results: Amongst 12, 385 patients suffering from SMI (64.1% schizophrenia spectrum and 36.9% bipolar spectrum disorders), 24% (range 21%–29%) died of cancer. In comparison with the general regional population, the mortality for cancer was about 50% higher among patients with SMI, irrespective if affected by schizophrenia or bipolar disorders. As for the site‐specific cancers, significant excesses were reported for stomach, central nervous system, respiratory, and pancreas cancer with a variability according to psychiatric diagnosis and gender. Conclusions: Patients suffering from SMI had higher mortality risk than the regional population with some differences according to cancer type, gender, and psychiatric diagnosis. Proper cancer preventive and treatment interventions, including more effective risk modification strategies (e.g., smoking cessation, dietary habits) and screening for cancer, should be part of the agenda of all mental health departments in conjunction with other health care organizations, including psycho‐oncology.